De un estado excluyente a un estado intercultural: Parte IV - Román Márquez, Álvaro (2024)
Although they have passed about seven years of existence and validlty of the Constitution of !he Republic of Ecuador we can not yel dare to say that the law is equal validity with its sociological validity. On leading lnstitutions having their statements in accordance with the constilulional movement neo that left its mark on almosl ali constitulions in Latín America there is a high dose of disbelíef in a broad sector of political and academic opinion still reluctant to find the desired transformation the foundations on which our rule of law is based.One of !hose píllars that collects new constitulíonal neo charge of the constitution has to do with the lssue of multiculturalism and legal pluralism, principies upon which the ordinary and indigenous justice as two complementary sources of independent law is built and hierarchically homogeneous. Multiculturalisrn as the suprema ideal hasits pitfalls in the constitutional and legal rules themselves resistan! to accept a theoretical construct law that requires genuine participation of ali peoples and nationalities that make up our soclety in the establishment, structure of ali state institutionsand the obiigatory presence they should have in the design and implementation of publíc policies that go beyond the mere discursive level.